INFLUENCE OF PALM OIL PALM CONSUMPTION WITH ADHESITATING BASED ON POLYPROPYLENE AND POLYPROPYLENE GRAFTING MALEAT ANHIDRAT - Adiansyah ,; Darwin Yunus; Marpongahtun , (AGRIUM: Jurnal Ilmu Pertanian, 2017)
The preparation and characterization of particle board from oil palm stem powders (Elaeis Guineensis Jacq) with polypropylene based adhesive and polypropylene grafting maleic anhydride was carried out with water immersion variation at 60 ° C and using 1% NaOH respectively for 24 hours. The results showed maximum MoR value for 1% NaOH immersion particle board at 430.11 kgf / cm2, density 0.54 g / cm3, water absorption 0.58%, and 0.47% thick development. For maximum particle particle MoE value of 10551.09 kgf / cm2 of density 0.63 g / cm3, 0.61% water absorption, and 0.49% thickness development, the results of this test meets the requirements of SNI 03-2105-2006. The FT-IR analysis shows typical uptake peaks at 3345.21 cm-1 and 1722.07 cm-1 which indicate the vibration of the hydroxyl group of palm oil cellulose and the vibration of the carbonyl ester group formed from the reaction of the maleic group with the hydroxyl group of the wood pulverized cellulose . The SEM analysis shows a homogeneous surface against a particle board with 1% NaOH immersion. TGA analysis of 1% NaOH particle gives two vertices of thermogravimetric curve, the first stage is 144.72oC - 166.13oC with a mass decrease of 5.596% (0.6966 mg) and in the second stage 200oC-358.23oC there is a mass decrease of 30.15% (3.753 mg) Residue of 10.97% (1.365 mg).Keywords: Polypropylene, PP-G-AM, Palm Oil Powder